2009
DOI: 10.1038/nature07746
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of HIV-1 to human leukocyte antigen class I

Abstract: The rapid and extensive spread of the human immunodeficiency virus (HIV) epidemic provides a rare opportunity to witness host–pathogen co-evolution involving humans. A focal point is the interaction between genes encoding human leukocyte antigen (HLA) and those encoding HIV proteins. HLA molecules present fragments (epitopes) of HIV proteins on the surface of infected cells to enable immune recognition and killing by CD8+ T cells; particular HLA molecules, such as HLA-B*57, HLA-B*27 and HLA-B*51, are more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
443
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 412 publications
(480 citation statements)
references
References 30 publications
(64 reference statements)
31
443
3
1
Order By: Relevance
“…By extension, HIV sequences circulating in a given host population exhibit polymorphisms that reflect the HLA allele distribution of that population (9). Because HLA class I allele distributions differ among racial and ethnic groups worldwide (10), the pattern and diversity of HLA-associated escape mutations are also likely to be somewhat distinct to each race and region.…”
mentioning
confidence: 99%
“…By extension, HIV sequences circulating in a given host population exhibit polymorphisms that reflect the HLA allele distribution of that population (9). Because HLA class I allele distributions differ among racial and ethnic groups worldwide (10), the pattern and diversity of HLA-associated escape mutations are also likely to be somewhat distinct to each race and region.…”
mentioning
confidence: 99%
“…Examples include viral adaptation during infection (1), the emergence of antibiotic resistance (2), artificial selection in biotechnology (3), and cancer (4). Rapid adaptation is characterized by three key features: (i) the availability of strongly advantageous traits accessible by rare mutations, (ii) an elevated mutation rate (1), and (iii) a dynamic population size (5). Because traditional theories of gradual adaptation are not applicable under these conditions, new approaches are needed.…”
mentioning
confidence: 99%
“…Taken together, our results showed that EBOV does not appear to be under diversifying selection pressure, but under purifying selection that appears to be the driving force on their protein coding genes. Results provided an alternative perspective than the current prevailing hypothesis that genes encoding antigens can be highly variable to evade host immunity [5,9,16]. Moreover, the synonymous nucleotide changes could also exert modifications to the secondary structure of regulatory cis-RNA sequences.…”
Section: Discussionmentioning
confidence: 90%